Prehospital tirofiban increases the rate of disrupted myocardial infarction in patients with ST-segment elevation myocardial infarction: insights from the On-TIME 2 trial - Rikken, Sem A. O. F.; Fabris, Enrico; Rosenqvist, Tobias; Giannitsis, Evangelos; ten Berg, Jurriën M; Hamm, Christian; van ‘t Hof, Arnoud (European heart journal - acute cardiovascular care, 2024)
In patients with ST-segment elevation myocardial infarction (STEMI), prehospital tirofiban significantly improved myocardial reperfusion. However, its impact on the rate of disrupted myocardial infarction (MI), particularly in the context of high-sensitivity cardiac troponin (hs-cTn) assays, is still unclear.The On-TIME 2 (Ongoing Tirofiban In Myocardial infarction Evaluation 2) trial randomly assigned STEMI patients to prehospital tirofiban or placebo before transportation to a percutaneous coronary intervention (PCI) centre. In this post hoc analysis, we evaluated STEMI patients that underwent primary PCI and had measured hs-cTn levels. Troponin T levels were collected at 18-24 and 72-96 h after PCI. Disrupted MI was defined as peak hs-cTn T levels ≤ 10 times the upper limit of normal (≤140 ng/L). Out of 786 STEMI patients, 47 (6%) had a disrupted MI. Disrupted MI occurred in 31 of 386 patients (8.0%) in the tirofiban arm and in 16 of 400 patients (4.0%) in the placebo arm (P = 0.026). After multivariate adjustment, prehospital tirofiban remained independently associated with disrupted MI (odds ratio 2.03; 95% confidence interval 1.10-3.87; P = 0.027). None of the patients with disrupted MI died during the 1-year follow-up, compared with a mortality rate of 2.6% among those without disrupted MI.Among STEMI patients undergoing primary PCI, the use of prehospital tirofiban was independently associated with a higher rate of disrupted MI. These results, highlighting a potential benefit, underscore the need for future research focusing on innovative pre-treatment approaches that may increase the rate of disrupted MI.